2014
DOI: 10.3138/jvme.0913-136r1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Canine Laparoscopic Simulator for Veterinary Clinical Training

Abstract: Human laparoscopic simulators have been used in medical education for minimally invasive surgery (MIS) in the past years. Simulator-based laparoscopic training has attracted much interest because unique skills have to be learned not only by surgeons in training but also by surgeons in practice. MIS forces the surgeon to adapt to monocular vision and decreased tactile sensation and entails training and improving hand-eye and hand-hand coordination. Those skills require a learning curve that could be overcome gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…24 The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training. [36][37][38][39][40][41] Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…24 The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training. [36][37][38][39][40][41] Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost. In human surgery, training courses that use mainly simulators are included in the orthopedic surgeon curriculum of some faculties.…”
Section: Discussionmentioning
confidence: 55%
“…The overall lack of availability and use of simulators reported in this study suggests that there is limited appreciation of the types and merits of simulator training along with concerns regarding financial and time investment . The results of the survey strongly support the introduction of structured simulator training in veterinary residency programs, as has recently been developed for laparoscopic training . Our results also suggest that external training courses that used simulator training were highly valued by the majority of participants, although they were not attended because of lack of time and cost.…”
Section: Discussionmentioning
confidence: 60%
“…Simulation training preferably starts early in the career of the MIS surgeon, ideally before or simultaneously with the first exposure to MIS in the operating room . To date, there is sparse information on skills training in veterinary medicine . The optimal design of a laparoscopic skills training program for veterinary surgeons remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…8 To date, there is sparse information on skills training in veterinary medicine. 27,[39][40][41][42][43][44] The optimal design of a laparoscopic skills training program for veterinary surgeons remains to be elucidated. Based on our previous research, 39,45 a more diverse training modality could enhance the training effect and combinations of different training modalities may be advantageous 45 for obtaining MIS skills.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of laparoscopic skills are important for validation of training programs, but also to verify an individual's manual skills competency. Research over the past two decades has reported on laparoscopic training and assessment modalities in human medicine, as is now emerging in veterinary medicine …”
mentioning
confidence: 99%